Transvesical route for NOTES urological applications: advances & controversies - Lima, Estêvão Augusto Rodrigues de (2012)
Natural Orifice Transluminal Endoscopic Surgery (NOTES) has emerged recently in the experimental surgical field, innovating for the passage of luminal barrier, the absence of scars and reduction of post-operative pain. Among the various ports of access (transvaginal, transgastric, transvesical and transcolonic), this paper is an update on advances & controversies of transvesical port for NOTES Urological applications.